Dietary Protein Intake and Survival in 100,088 Maintenance Hemodialysis Patients: The Role of Race and Albumin - Vanessa Ravel; Miklos Z Molnar; Jennie Jing; Elani Streja; Alla Victoroff; Csaba P Kovesdy; Keith C Norris; Joel D Kopple; Debbie Benner; Jun Chul Kim; Kamyar Kalantar-Zadeh (The Korean Society of Nephrology, 2012)
Decreased dietary protein intake may be associated with increased mortality risk in individuals undergoing maintenance hemodialysis (MHD). We examined 8−year all-cause mortality in 100,088 MHD patients from DaVita dialysis clinics in the US (2001-2009) and hypothesized that survival is better across higher levels of nPNA, (nPCR, a dietary protein intake surrogate) with consistent trends across race and in hypoalbuminemic patients. Time-averaged Cox models were used to estimate death hazard ratios for quarterly averaged nPNA categories controlled for case-mix, comorbidity, dialysis dose, and available markers of malnutrition-inflammation-complex syndrome (MICS). In all patients, both low (<0.6 g/kg/day, HR 1.53, [1.47-1.59]) and high nPNA (≥1.4 g/kg/day, HR 1.26, [1.19-1.34]) were associated with higher all-cause mortality when compared with the reference (1.0-<1.1 g/kg/day). This reverse-J-shape association was also found in sub-analyses performed among racial groups and in hypoalbuminemic patients (Figure). Hence, hypoalbuminemic patients of all races may benefit from higher protein intake, which needs controlled trial to verify.